Coproducción de imaginarios de justicia hídrica y desarrollo verde en Ecuador - Dupuits, Emilie (European Review of Latin American and Caribbean Studies, 2021)
Abstract: Coproducing imaginaries on water justice and green development in EcuadorFacing water injustices and extractivist policies, grassroots movements of the province of Imbabura, in the northern highlands of Ecuador, are seeking to participate in and benefit from green infrastructure projects. Both the Pesillo-Imbabura regional drinking water project and the HidroIntag mini hydraulic plants project illustrate this trend. However, grassroots movements often have to negotiate their initial claims in order to get involved in these projects. To what extent the coproduction of sociotechnical imaginaries linked to green infrastructure projects transform water justice grassroots movements’ claims and strategies? What are the counterimaginaries that emerge at the margins of these modernizing pro-cesses? This paper analyses, from a political ecology and feminist technoscience perspectives, how the participation of water grassroots movements in green infrastructure projects means the coproduction of sociotechnical imaginaries with public authorities, private companies or development agencies, the transformation of their initial territorial claims and the emergence of counterimaginaries by resisting actors.ResumenEn un contexto de injusticia hídrica y de extractivismo, varios movimientos comunitarios de la provincia de Imbabura, en la sierra norte del Ecuador, buscan participar en y beneficiarse de proyectos de desarrollo verde. Tanto el proyecto regional de agua potable Pesillo-Imbabura como el proyecto de minicentrales hidroeléctricas HidroIntag ilustran esa tendencia. Sin embargo, los movimientos comunitarios se ven obligados a negociar sus demandas iniciales para estar incluidos en esos proyectos. ¿En qué medida la coproducción de imaginarios sociotécnicos asociados a proyectos de desarrollo verde transforma las demandas y estrategias de los movimientos comunitarios por la justicia hídrica? ¿Cuáles son los contra-imaginarios producidos en la periferia de esos procesos modernizadores? Este artículo analiza, desde una perspectiva de ecología política, cómo la participación de los movimientos comunitarios por el agua en proyectos de desarrollo verde implica la coproducción de imaginarios sociotécnicos con las autoridades públicas, la empresa privada y las agencias de desarrollo, la transformación de sus demandes territoriales iniciales y la emergencia de contraimaginarios por actores resistentes.